Development of G-Sites that Support Students' Self-Regulated Learning Using TGT Type of Cooperative Learning - Rizqi, Abdur Rahman; Widarti, Hayuni Retno; Anantayani, Aisyah; Nisa, Afina Afidhotun; Amrullah, Nur Kholish; Aini, Rofinda Gita (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Independence in learning can be built through self-regulated learning. The low of student self-regulated learning occurred in students of class X.1Â State Senor High School (SMAN)Â 6 Malang. So far, research related to improving students' self-regulated learning has only focused on strategies without supporting learning media. Therefore, it is necessary to conduct a research and development study on instructional media that can enhance students' self-regulated learning. The purpose of this study is to develop a G-Sites-based learning media integrated with the TGT type of cooperative learning model to improve students' self-regulated learning. This study employs the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation, carried out systematically. The sampling technique used in this study is purposive sampling, as the research is based on a problem related to low self-regulated learning identified in class X.1. The subjects of this research were students of class X.1, students of class XI as respondents of readability test, and chemistry teachers of SMAN 6 Malang as validators of material and media experts. Data analysis was carried out using a mixed-method approach, both qualitative and quantitative, employing descriptive and percentage analysis techniques. The developed product was declared valid and feasible to use with percentage results on the graphic design aspect of 83%; presentation and use of media 80%; suitability of material 97%; presentation of material 93%; language 88%; suitability of syntax 97%; and suitability of self-regulated learning 100%. The implementation of G-Sites is proven to increase students' self-regulated learning by 14.5%.